Heeding the corpse in the cargo: The writing centre and the need to listen - Nichols, Pamela (South African Journal of Higher Education, 2016)
Transformation is perhaps an overused word. It is not written in our constitution though it is used daily by politicians in the ANC. The eyes of many South Africans become glazed when they hear it. Yet it is crucial in a country which is still poised between chaos and progress, which still has the potential to dissolve into race related riots or build itself into a creative multicultural democracy. What might it mean specifically in terms of hopeful strategies at the Wits Writing Centre? This paper seeks to first describe through a short ethnographic description of cultural pattern, as modelled by Jones, Lea and Street (1998) elements of cultural stasis within the greater institutionalised culture of teaching and learning. Then using Jonathan Jansen’s theorising of embedded knowledges in contemporary South African universities (2009) it identifies types of knowledge present in this particular cultural pattern which repel change. The writing centre is understood through eco composition (De Wet 2011) as a small pocket within this macro environment which interacts with these often invisible and controlling knowledges present in our context. What can this pocket do to resist the overwhelming inertia of embedded knowledge and construct and maintain a space which allows for change? It will be argued that the primacy of the art of listening and the welcoming of opportunities for reflecting on dissonance, allows for the space of the writing centre to disrupt what Jansen terms ‘knowledge in the blood’.